The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1002/cplu.202000553
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene Tetramerisation: A Structure‐Selectivity Correlation

Abstract: The effect of ethylene tetramerisation ligand structures on 1‐octene selectivity is well studied. However, by‐product formation is less understood. In this work, a range of PNP ligand structures are correlated with the full product selectivity and with catalyst activity. As steric bulk on the N‐substituent increases, the product selectivity shifts from >10 % to < 3% of both C6 cyclics and C16+ by‐products. 1‐Octene peaks at ca. 70%. Thereafter, only 1‐hexene increases. Similar selectivity changes were observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 48 publications
1
9
0
Order By: Relevance
“…Complex 9 afforded the 58.6% selectivity toward C 8 and the 24.7% selectivity toward C 6 (45.8% 1-C 6 ). These results demonstrated that the catalytic activity and the production selectivity were mainly dependent on the electron-donating property and the steric bulk in ligands 1–3 , which was in line with the literature results. , To summarize, the experimental results also revealed that complex 7 can promote the nonselective ethylene oligomerization, while both complex 8 and complex 9 are more beneficial for the selective ethylene tri/tetramerization. Since complex 8 presented the highest C 8 selectivity and the lowest PE content, it was selected to further explore the effect of reaction conditions on the catalytic selective ethylene tri/tetramerization.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Complex 9 afforded the 58.6% selectivity toward C 8 and the 24.7% selectivity toward C 6 (45.8% 1-C 6 ). These results demonstrated that the catalytic activity and the production selectivity were mainly dependent on the electron-donating property and the steric bulk in ligands 1–3 , which was in line with the literature results. , To summarize, the experimental results also revealed that complex 7 can promote the nonselective ethylene oligomerization, while both complex 8 and complex 9 are more beneficial for the selective ethylene tri/tetramerization. Since complex 8 presented the highest C 8 selectivity and the lowest PE content, it was selected to further explore the effect of reaction conditions on the catalytic selective ethylene tri/tetramerization.…”
Section: Resultssupporting
confidence: 90%
“…The effects of reaction conditions, including the oligomerization temperature, reaction pressure, and Al/Cr molar ratio, on the catalytic selective ethylene tri/tetramerization were studied with the complex 8/MAO system to achieve the optimal catalytic response. First, the different oligomerization temperatures (40,45,50, and 55 °C) were evaluated, as shown in Figure 2a. The catalytic activity of the complex 8/ MAO system showed a volcano shape with increasing reaction temperatures from 40 to 55 °C, and the highest catalytic activity of 201.9 kg/(g Cr•h) was obtained at 45 °C.…”
Section: Effect Of Reaction Conditions On the Catalytic Behaviorsmentioning
confidence: 99%
See 1 more Smart Citation
“…54 Experimentally, Makume examined purity for ethylene tetramerization with bisphosphine Cr catalysts where the steric bulk on the N-position of the ligand backbone partially controls purity. 55 As one recent example from a computational perspective, Liu and Liu used DFT calculations to understand trimerization/tetramerization selectivity for (2,2-dipicolylamine)Cr catalysts, 56,57 and in addition to the Cr charge controlling selectivity it was proposed that steric effects impact 1-hexene selectivity.…”
Section: Catalystmentioning
confidence: 99%
“…Owing to the superior material properties of the copolymers derived from 1-hexene/1-octene over other alpha olefins, the search for a catalytic system to selectively produce C 6 /C 8 a-olefins via ethylene tri-/tetramerization has witnessed a steady upsurge in recent years. [1][2][3][4][5][6][7] Most notably, following the emergence of Sasol's initial reports on tetramerization, the chromium-based pre-catalysts where the metal center is stabilized by bidentate phosphine ligands, [8][9][10][11][12][13][14][15][16][17][18] in particular bisphosphineamines (PNPs), [8][9][10][11][12] have received considerable attention. Since the N-substituents of the PNP ligands are believed to play a critical role in oligomerization performance, numerous N-functionalized PNP ligands have been developed and investigated for this purpose.…”
mentioning
confidence: 99%